1997
DOI: 10.1093/oxfordjournals.pcp.a029193
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of a MADS-Box cDNA Clone of the Fuji Apple

Abstract: A cDNA clone, MdMADS1, containing MADS domain was isolated from the Fuji apple. The gene was expressed in all floral organs and young fruits but not in leaves. The expression was higher at the early stages of flower and fruit developments, suggesting that MdMADS1 plays a major role in the initiation of reproductive organ developments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…The factors that affect the formation of flowers in apple trees are of particular interest in horticulture, but relatively little attention has been given to the molecular and genetic control of apple flower development. We previously isolated and characterized a MADS-box gene, Md-MADS1, from Fuji apple, which was classified as a member of the AGL2 subfamily (Sung and An, 1997). In the present study, we report characteristics of another MADS-box gene from Fuji apple, MdMADS2, which shows high sequence similarities to the SQUA subfamily genes.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…The factors that affect the formation of flowers in apple trees are of particular interest in horticulture, but relatively little attention has been given to the molecular and genetic control of apple flower development. We previously isolated and characterized a MADS-box gene, Md-MADS1, from Fuji apple, which was classified as a member of the AGL2 subfamily (Sung and An, 1997). In the present study, we report characteristics of another MADS-box gene from Fuji apple, MdMADS2, which shows high sequence similarities to the SQUA subfamily genes.…”
mentioning
confidence: 68%
“…The flower buds were sampled on the basis of the bud length and morphological events, as previously described (Sung and An, 1997). As shown in Figure 2, the MdMADS2 mRNA was not detectable in mature leaves (lane 1), whereas the transcript was detected in flower buds at all five stages of flower development (lanes 2-6).…”
Section: Rna Blot Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…Such genes are isolated from flower buds in the still initial phases of their development, from flower organs and fruits of some apple cultivars (68,110,111,118,129).…”
Section: Development Of the Flower Budsmentioning
confidence: 99%
“…It has been found that MADS-box proteins play a crucial role in flower and fruit development [21][22][23][24][25]. Although the main studies on fruit have been performed on tomato, which is a berry, there are reports indicating that the mechanisms are conserved, at least partially, in other fruit such as banana [26], grape berry [27][28][29], peach [30] cucumber [31] and apple [17,[32][33][34][35]. MADS-boxes have also been found involved in vegetative processes [36][37][38][39] with good conservation of activity [40,41].…”
Section: Introductionmentioning
confidence: 99%